(untitled) (Revista Innova Educación, 2022)
Early childhood education is the stage in which the training process occurs in children from birth to the age of six, it seeks physical, affective, social, and intellectual development, incorporates guidelines for coexistence, based on respect to differences, development of affective capacities, and democratic values that facilitate social interaction. The research that supports this article aims to understand in depth the pedagogical, epistemic, didactic, neuropedagogical, and autodidactic strategies that reorient the teacher’s action in the processes of educability and teachability in the area of social sciences and early childhood education. It is approached from an action research - reflection, directed from a comprehensive interpretive method with a bibliographic design. The result is that social thought is enhanced and developed from a pedagogical and didactic praxis pertinent to the nature, essence, and context of the child. It reaches the conclusion of de-instrumentalizing the processes of educability and teachability and placing the human being at the center of the educational process as a multidimensional situated being, that is, a bio-psycho-neurocultural being.